Link's international dictionary of business economics - Link, Albert N. (Chicago, Ill. : Probus Pub. Co., 1993)
This volume contains approximately 2,500 of the most frequently used business economics terms and phrases. Emphasis has been placed not only on the inclusion Of international terms and phrases, but also on institutional facts germane to a variety of nations and on statistical methods as related to business economics matters.
ne 25/08/2021
Ref.
Keywords: Managerial economics